2018
DOI: 10.1016/j.jecp.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Supporting cognitive control through competition and cooperation in childhood

Abstract: Cognitive control is often engaged in social contexts where actions are socially relevant. Yet, little is known about the immediate influence of the social context on childhood cognitive control. To examine whether competition or cooperation can enhance cognitive control, preschool and school-age children completed the AX Continuous Performance Task (AX-CPT) in competitive, cooperative, and neutral contexts. Children made fewer errors, responded faster, and engaged more cognitive effort, as shown by greater pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
3
5
0
Order By: Relevance
“…In this study, we argue that this balancing was reflected by sensitivity to the opportunity cost of time, whereby older adults engaged in cognitive effort when it was most rewarding when the average reward rate was high. In this way, our findings join a spate of recent work that suggests that people can adaptively change behaviour to overcome age-related cognitive limitations if properly incentivised to do so (Ferdinand & Czernochowski, 2018;Yee et al, 2019;Patzelt et al, 2019;Harsay et al, 2010;Gatzke-Kopp, 2018;Chevalier, 2015;Niebaum et al, 2019;Fischer et al, 2018). We extend this work by suggesting a potential computational mechanism that older adults (and possibly children) use to strategically adapt to cognitive control demands in their environment: the opportunity cost of time.…”
Section: Summary Of Resultssupporting
confidence: 76%
“…In this study, we argue that this balancing was reflected by sensitivity to the opportunity cost of time, whereby older adults engaged in cognitive effort when it was most rewarding when the average reward rate was high. In this way, our findings join a spate of recent work that suggests that people can adaptively change behaviour to overcome age-related cognitive limitations if properly incentivised to do so (Ferdinand & Czernochowski, 2018;Yee et al, 2019;Patzelt et al, 2019;Harsay et al, 2010;Gatzke-Kopp, 2018;Chevalier, 2015;Niebaum et al, 2019;Fischer et al, 2018). We extend this work by suggesting a potential computational mechanism that older adults (and possibly children) use to strategically adapt to cognitive control demands in their environment: the opportunity cost of time.…”
Section: Summary Of Resultssupporting
confidence: 76%
“…There is a vast literature documenting the relationship between classroom climate and knowledge of student cognition at the primary school level (Fischer et al, 2018), secondary school level (Erdogan, 2019;Liu & Su, 2018;Zepeda et al, 2018) as well as the higher institutional level (Mccleary et al, 2019;Salam et al, 2020;Sugiharto et al, 2018). Further, recent empirical studies have confirmed there is a positive relationship between metacognition and achievement in many subject areas, such as science subject (Ellah et al, 2018;Langdon et al, 2019), mathematics subject (Bishara & Kaplan, 2018;Nurulhuda & Saemah Rahman, 2017;Riyan Hidayat et al, 2018;Al-Shabibi & Alkharusi, 2018) and language subject (Ghaith & El-Sanyoura, 2019).…”
Section: Mediation Effect Of Knowledge Of Cognition In Classroom Clim...mentioning
confidence: 99%
“…Extensive of studies revealed important findings related to classroom climate and regulation cognition (Alzahrani, 2017;Cayubit, 2021;Fathi & Shabani, 2020;Fischer et al, 2018;Hafızoglu & Yerdelen, 2019;Liu & Su, 2018) which have received adequate attention from the researchers and practitioners. Moreover, it should be noted that regulation cognition has been widely recognised as a potential predictor of the students' achievement (Izzati & Mahmudi, 2018;Mirhosseini et al, 2018;Mohamad Ariffin & Norulhuda, 2020).…”
Section: Mediation Effect Of Regulation Cognition In Classroom Climat...mentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, the presence and behaviour of others can influence our own decisions [15]. For example, children engage higher cognitive control when competing or cooperating with another person [16] and are less likely to delay gratification when the experimenter behaves in an unreliable/ untrustworthy manner [17]. Flexibility in self-control is likely to be important in a social context in non-human animals too, for instance, refraining from approaching food or a potential mate while in the presence of a competitor [18,19].…”
Section: Introductionmentioning
confidence: 99%